ACOMPARATIVEEVALUATION OF SPERMQUALITYFROMPOOLED SEQUENTIALEJACUL ATES OF MENWITHNORMALANDABNORMALSEMEN - Kaluarachchi, A; Wijerathne, S; Senavirathne, H.R; Nelson, C; Lankeshwara, D; Rajapakse, S (My University)
Male factor contribution among infertile couples is around 60% as a single entity or combined with female factors. Assisted reproduction technology, Intra Uterine Insemination in particular, has become a mainstay therapy in treatment of male infertility. Harvesting the maximum quantity of good quality spermatozoa is of extreme importance in managing male infertility using Assisted Reproductive Technologies.